Integrity in scientific research : creating an environment that promotes responsible conduct (National Academies Press, 2002)
"Integrity in Scientific Research attempts to define and describe those elements that enable and encourage individuals involved with scientific research to act with integrity. Providing a framework for research and educational institutions, this important book will be essential for anyone concerned about ethics in the scientific community."--Jacket
"Support for this project was provided by the Office of Research Integrity, U.S. Department of Health and Human Services."--Title page verso
Keywords: Research -- Moral and ethical aspects.; Integrity.; Fraud in science.; Research -- standards; Ethics; Research Personnel; Ethics, Institutional; Social Control, Informal; Scientific Misconduct; United States; Recherche -- Aspect moral.; Intégrité.; Fraude scientifique.; BUSINESS & ECONOMICS -- Business Ethics.; Fraud in science; Integrity; Research -- Moral and ethical aspects; Integriteit.; Onderzoek.; Wetenschapsbeleid.; 02.15 science policy, cultural policy.; Wissenschaftsethik.